Cosmological Orientation in Promoting the Enrollment in Short-Term Mobile Skill-Trainings: A Narrative Inquiry on Women's Lives in Nepal (Journal of Training and Development, 2019)
The Government of Nepal has prioritized the need of mobile skill-training program for imparting the skill-training opportunities to the potential beneficiaries in their own settlement both in urban and rural areas. It is different from the centrally based training program as it is conducted by setting temporary training venues in particular settlement where the training participants are residing in the majority. This paper describes how adult women exhibit readiness to participate in the short-term mobile skill-training program in Nepal. The paper is based on a qualitative study with an interpretative paradigm following the narrative inquiry approach. The four participants were selected based on their experiences of receiving the training through mobile skill training program and currently employed in the trained trades. The interpretations of their life stories reveals that women in Nepal choose to enroll in the short-term mobile skill-training program as they believe it to be a gateway for them to get social recognition. Likewise, they prefer closer training venue and short duration training program due to their responsibilities towards their family. The findings of this research are useful in framing appropriate plans and policies for conducting short-term vocational training programs in mobile venues for bringing socio-economic changes in women's lives by respecting their family value system.